O miłości z gimnazjalistami. Projekt dydaktyczno-wychowawczy - Marzec, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The study carried out among students of gimnazjum school shows that the most widely accepted value for them is love. The article, therefore, aims to emphasise the need of including the value of love in the process of education. This issue should be the principle objective when working with gimnazjum students on culture texts in the lessons of Polish. The article contains suggestions concerning educational process in three theme cycles related to love: love of life, home and family, and other people.